Andragogy as a Knowledge Driving Discipline in Higher Education - Alonso Chacón, Paula (2012)
This paper exposes the diachronic (historical overview) of Andragogy (or Adult Education) and its introduction as a discipline in the context of university education. Based on the andragogical principles of the adult thought process and the work experience, this study sets out Adult Education as an education option to be implemented in higher education, in Costa Rica, to develop cognitive and meta-cognitive competencies in the university students, in the different academic areas simultaneously, by reproducing the Socratic maieutics, which is structured within the Kolb’s experiential learning cycle.